2019
DOI: 10.1002/mds.27653
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's disease in the United States: Variation by demographic and socioeconomic factors

Abstract: A BS TRACT: Background: Despite extensive research regarding the etiology of Huntington's disease, relatively little is known about the epidemiology of this rare disorder, particularly in the United States where there are no national-scale estimates of the disease. Objectives: To provide national-scale estimates of Huntington's disease in a U.S. population and to test whether disease rates are increasing, and whether frequency varies by race, ethnicity, or other factors. Methods: Using an insurance database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 44 publications
0
39
1
2
Order By: Relevance
“…In the population of the United States from 2003 to 2016 the incidence rate was 1.22 per 100 000 personyears [23] while in Asian countries it is much lower (0.06 in Korea during 2009-2013 [24] and 0.1 in Taiwan during 2000-2007 [25]). In their review, Pringhsheim et al found a mean incidence of 0.4 per 100 000 person-years.…”
Section: Discussionmentioning
confidence: 94%
“…In the population of the United States from 2003 to 2016 the incidence rate was 1.22 per 100 000 personyears [23] while in Asian countries it is much lower (0.06 in Korea during 2009-2013 [24] and 0.1 in Taiwan during 2000-2007 [25]). In their review, Pringhsheim et al found a mean incidence of 0.4 per 100 000 person-years.…”
Section: Discussionmentioning
confidence: 94%
“…In the population of the United States from 2003 to 2016 the incidence rate was 1.22 per 100.000 personyears [24] while in Asian countries it is much lower (0.06 in Korea during 2009-2013 [25] and 0.1 in Taiwan during 2000-2007 [26]). In their review, Pringhsheim et al found a mean incidence of 0.4 per 100.0000 person-years.…”
Section: Discussionmentioning
confidence: 95%
“…In the population of the United States from 2003 to 2016 the incidence rate was 1.22 per 100,000 person-years [ 23 ] while in Asian countries it is much lower (0.06 in Korea during 2009–2013 [ 24 ] and 0.1 in Taiwan during 2000–2007 [ 25 ]). In their review, Pringsheim et al found a mean incidence of 0.4 per 100,000 person-years.…”
Section: Discussionmentioning
confidence: 99%